UPAYA MENINGKATKAN MOTIVASI BELAJAR MATEMATIKA SISWA KELAS X SMA NEGERI 2 MUARA BUNGO MELALUI PELAKSANAAN TEAM TEACHING - Afriyenti, Eva (Prodi Pendidikan matematika Universitas Islam Majapahit (UNIM), Mojokerto, Indonesia, 2020)
This research was conducted with the aim to increase the mathematics motivation of students of class X A of SMA Negeri 2 Muara Bungo through teaching learning and to describe the increased motivation of mathematics learning in class X A of Senior High School in Muara Bungo.This research is a Classroom Action Research. The subjects of this study were class X A students, amounting to 32 students. The study was conducted in two cycles and each cycle consisted of two meetings. Data collection techniques in this study used observation and research. The data obtained were analyzed by means of reduction, data exposure and conclusion. Descriptive data analysis was also carried out for observational data. Based on the results of the study, it was concluded that the implementation of teaching in order to increase motivation to learn mathematics. From the results of observations of the implementation of team teaching, in the first cycle reached 90.48% and 100% in the second cycle. The results showed that there was an increase in student motivation as indicated by the average size of the percentage in student learning questionnaires, namely overall in the first cycle of 74.41% with the medium category being 87.28% with a high category in the second cycle.